Implementasi Metode At-Tanzil dalam Pembelajaran BTQ di Sanggar Bimbingan At-Tanzil, Malaysia - Nabilla Fahrani; Rina Priarni; Isnaini (Jurnal Ragam Pengabdian, 2026)
Learning to read the Qur'an is an important aspect of Islamic education because it aims to develop students' ability to read the Qur'an correctly according to tajwid rules. However, Qur'an learning in non-formal educational institutions still faces various challenges, such as differences in students' abilities, inconsistencies in learning participation, and limited teaching methods. One of the learning approaches used is the At-Tanzil method, which emphasizes systematic and gradual learning from recognizing hijaiyah letters to reading Qur'anic verses with proper pronunciation. This study aims to analyze the implementation of the At- Tanzil method in Qur'an learning (BTQ) at Sanggar Bimbingan At-Tanzil Malaysia. This research uses a qualitative field research approach. Data were collected through observation, interviews, and documentation. The data analysis technique used includes data reduction, data presentation, and conclusion drawing. The results of the study show that the implementation of the At-Tanzil method helps students improve their ability to read the Qur'an gradually through structured learning stages, intensive guidance, and repeated reading practice. However, several obstacles were found, such as linguistic influences in pronunciation and differences in students' learning abilities. Overall, the At-Tanzil method provides positive contributions to improving students' Qur'an reading skills.